2021
DOI: 10.3906/zoo-2007-8
|View full text |Cite
|
Sign up to set email alerts
|

Status and distribution of the Striped Hyaena, Hyaena hyaena, in Turkey: an updated assessment (Carnivora: Mammalia)

Abstract: The Striped Hyaena, Hyaena hyaena, extends its distribution in the north into Turkey, where it has always been rare. In a status assessment conducted by Kasparek et al. in 2004, it was shown that the species is at the brink of extinction. We compiled information from different sources including a press survey and camera trapping in different parts of the country. The situation has even deteriorated since then. The population has strongly decreased, in particular in the Marmara and Mediterranean regions, and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…2021, Çoğal et al. 2021) outside of protected areas, and as human–hyaena spatial overlap increases, more research on human perspectives towards striped hyaena and fine‐scale striped hyaena behaviour may foster coexistence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2021, Çoğal et al. 2021) outside of protected areas, and as human–hyaena spatial overlap increases, more research on human perspectives towards striped hyaena and fine‐scale striped hyaena behaviour may foster coexistence.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a combination of reduced habitat and prey availability, along with an affinity for anthropogenic attractants, can result in conflicts with striped hyaena (Mills & Hofer 1998, Bhandari et al 2021. As striped hyaena continue to be reported in new locations (Akash et al 2021, Bhandari et al 2021, Çoğal et al 2021) outside of protected areas, and as human-hyaena spatial overlap increases, more research on human perspectives towards striped hyaena and fine-scale striped hyaena behaviour may foster coexistence.…”
Section: Trends In Striped Hyaena Researchmentioning
confidence: 99%
“…The species' geographic distribution stretches across northern and eastern Africa, the Middle East, south‐central Asia, and almost the entire Indian subcontinent (Hofer & Mills, 1998a). However, many populations are disjunct, and the distribution is discontinuous (Cogal et al, 2021; Hadad, 2021). Indeed, regional studies showed, for example that the species in Armenia is nearly extinct (Khorozyan et al, 2011), and in Nepal, it is decreasing rapidly (Bhandari et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In most countries of the Middle East, the status of the striped hyena ranges from Vulnerable to Critically Endangered (Abi‐Said, 2006; Almasieh et al, 2022; Cogal et al, 2021; von Jaffa, 2020), including also in Israel (Dolev & Pervolutzky, 2002). The conservation status mainly results from habitat fragmentation of optimal habitats (Almasieh et al, 2022; Cogal et al, 2021) and human persecution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation